Hyperbaric Oxygen Treatment Improves Intestinal Barrier Function After Spinal Cord Injury in Rats - Liu, Xuehua; Liang, Fang; Zhang, Jing; Li, Zhuo; Yang, Jing; Kang, Nan (Frontiers in Neurology, 2020)
Intestinal barrier dysfunction is often observed clinically after spinal cord injury (SCI) and seriously affects long-term quality of life. Hyperbaric oxygen (HBO) treatment has been proved to promote barrier function recovery after injury, but the influence of HBO on intestinal barrier function following SCI is unclear. We aimed to investigate the effect and mechanisms of HBO treatment on intestinal barrier function by measuring the level of tight junction (TJ) proteins and the Ras homolog (Rho)/Rho associated coiled-coil forming protein kinase (ROCK) signaling pathway. SCI model was established in rats, and the animals were randomly assigned into three groups: sham-operation group (SH), SCI group and SCI+HBO group. In the SCI+HBO group, the rats inhaled 100% O2 for 1 h at 2.0 ATA once per day after surgery. Neurological function and intestinal permeability were assessed after surgery, and the jejunum tissue was excised for histological and intestinal barrier function evaluation. The protein levels of TJ and the Rho/ROCK signaling pathway were also measured. The results showed that in the SCI group, intestinal mucosal injury score, intestinal permeability and levels of Rho and ROCK1 were higher, and TJ proteins Occludin and ZO-1 were lower than those in the SH group (P<0.01). HBO treatment significantly inhibited the expression of Rho and ROCK1, increased Occludin and ZO-1 expression, decreased intestinal permeability and alleviated intestinal mucosal injury compared to the SCI group (P<0.05, P<0.01). The SCI+HBO group showed higher Basso-Beattie-Bresnahan (BBB) scores relative to the SCI group on postoperative days 7 and 14 (P<0.01). There was a significantly negative correlation between BBB score and intestinal mucosal injury score in rats after HBO treatment (P<0.05).We concluded from this study that HBO treatment promoted the expression of TJ proteins possibly through inhibiting Rho/ROCK signaling pathway, which protected the intestinal barrier function and improved the intestinal permeability after SCI in rats.